A node failure and battery-aware coverage protocol for wireless sensor networks. (November 2017) - More, Avinash; Raisinghani, Vijay
Highlights: An algorithm to normalize a battery-discharge-curve, for computation of accurate wake-up time for inactive (SLEEPing) nodes. A bathtub-curve-based model for node failure probability. This model is further refined to compute the optimal wake-up time (Backoff Sleep Time). An algorithm for computing coverage redundancy using Received Signal Strength Indicator (RSSI) and message exchanges between neighboring ACTIVE nodes. Graphical abstract: Abstract: A typical wireless sensor network (WSN) is used to monitor or sense an area for events. Sensing-area coverage of a WSN is the collective sensing area of all the active nodes in the WSN. However, there might be a possibility of multiple active nodes monitoring the same area. This would result in energy wastage. Further, the sudden failure of nodes may result in coverage gaps within the sensing area. We propose Optimized Discharge-Curve-based Coverage Protocol (ODCP) to handle these problems. ODCP determines optimal sleep schedules for redundant nodes using their neighboring active nodes' battery discharge rate, failure probability, and coverage overlap information. ODCP is simulated extensively using various scenarios of WSNs. The simulation results show that ODCP provides energy-efficient coverage as compared to other existing coverage protocols.